2021
DOI: 10.1016/j.ijscr.2021.106322
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of recto-vaginal fistula (about 6 cases)

Abstract: Introduction Recto-vaginal fistula (RVF) is defined as a pathological epithelialized communication between the posterior wall of the vagina and the anterior wall of the rectum through the recto-vaginal septum. RVFs are rare and represent less than 5% of rectal fistulas. Occurring after childbirth or during a proctological pathology, they create a deep distress for the patients. The aim of our work is to analyze the epidemiological particularities and the risk factors of occurrence of RVF as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In an interesting and landmark study, Reisenauer reported on the transvaginal closure of the rectovaginal fistula with a success rate of 92.4% [16]. Transvaginal repair of VVF and RVF with an interposition flap has shown excellent results [12][13][14]19,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an interesting and landmark study, Reisenauer reported on the transvaginal closure of the rectovaginal fistula with a success rate of 92.4% [16]. Transvaginal repair of VVF and RVF with an interposition flap has shown excellent results [12][13][14]19,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The transvaginal repair of vesicovaginal and rectovaginal fistulas, either in one sitting (single operation) or two different operative sessions (staged repair), can be done with Martius flap interposition. The association of VVF with RVF is categorised as complicated VVF, and the success rate for VVF repair in such cases has been reported at more than 86% [ 12 , 13 ]. Apart from the Martius vascular pedicle flap, the gracilis muscle can also be used as an interposition flap [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ректовагинальные свищи классифицируются в зависимости от их расположения, размера и этиологии как простые или сложные свищи [1,23]. Классификация местоположения имеет важное значение, т. к. она определяет план лечения, поскольку свищ низкого типа может быть устранен с помощью местных или промежностных хирургических вмешательств, в то время как трансабдоминальный доступ обычно требуется для свищей высокого типа.…”
Section: классификацияunclassified
“…Ректовагинальный свищ (РВС) -патологическое эпителизированное сообщение между задней стенкой влагалища и передней стенкой прямой кишки через ректовагинальную перегородку [1].…”
Section: Introductionunclassified
See 1 more Smart Citation